1999
DOI: 10.1093/jn/129.4.883
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Intake of Food Bank Users Is Related to Frequency of Food Bank Use, Household Size, Smoking, Education and Country of Birth

Abstract: The number of individuals and families accessing food assistance programs has continued to grow throughout the 1990s. Despite the increased health risk among low-income people, few studies have addressed nutrient intake throughout the month or at the end of the month when food and financial resources are thought to be compromised, and no study has described dietary status of a random sample of food bank users. Nutrient intakes of adult female and male food bank users in metropolitan Montreal, Quebec, Canada, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 26 publications
3
25
1
2
Order By: Relevance
“…These results are consistent with other Canadian studies of food purchasing and food intake (Leaman and Evers, 1997;Jacobs Starkey et al, 1999;Jacobs Starkey and Kuhnlein, 2000;Tarasuk, 2001;Kirkpatrick and Tarasuk, 2003), showing compromised food selection among lowincome groups, with vegetables and fruit, and milk products identified as being particularly vulnerable to situations of low income. However, by using non-parametric statistical techniques, we have been able to discern an income threshold below which food purchasing appears to be severely constrained.…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with other Canadian studies of food purchasing and food intake (Leaman and Evers, 1997;Jacobs Starkey et al, 1999;Jacobs Starkey and Kuhnlein, 2000;Tarasuk, 2001;Kirkpatrick and Tarasuk, 2003), showing compromised food selection among lowincome groups, with vegetables and fruit, and milk products identified as being particularly vulnerable to situations of low income. However, by using non-parametric statistical techniques, we have been able to discern an income threshold below which food purchasing appears to be severely constrained.…”
Section: Discussionsupporting
confidence: 91%
“…A study of women in families using food banks in Toronto documented very low levels of calcium intake 17 and limited consumption of milk products 24 , while Jacobs Starkey et al 22 found low levels of calcium, vitamin A and zinc among food bank users in Montreal. The authors also found that their sample consumed fewer servings of milk products than did Quebecers in general 23 .…”
Section: )mentioning
confidence: 99%
“…Household characteristics have been shown to influence BMI through food availability, expenditure and behavior [20]. Participation in food programs, nutrient intake and income also vary by household [21]. Higher weights are found among adults in rural areas of the south, but race vary by race/ethnicity [22] While moving to a dense area often results in weight loss, high BMI individuals are unlikely to choose these areas [23].…”
Section: Covariatesmentioning
confidence: 99%